Effect of terthiophene spacer position in Ru(II) bipyridyl complexes on the photocurrent and photovoltage for high efficiency dye-sensitized solar cells. (September 2018) - Elmorsy, Mohamed R.; Su, Rui; Fadda, Ahmed A.; Etman, H.A.; Tawfik, Eman H.; El-Shafei, Ahmed
Abstract: Two novel ruthenium complexes, MR-1 and MR-2 were synthesized for use in dye-sensitized solar cells (DSSCs). Under similar fabrication conditions, the photovoltaic performances of these dyes were evaluated and compared to the standard ruthenium complex N719. MR-1 and MR-2 showed the efficiencies of 8.19% and 5.32%, respectively, while N719 achieved 7.66%. MR-1 also displayed higher V OC than MR-2, which is due to the larger molecular size and higher molar extinction coefficient of the former, which translates into less dye aggregation on a thinner film of TiO2 . Incorporation of terthiophene as a linker reduces the band gap of MR-1 when compared to that of MR-2. The influence of π-conjugated bridge on optical and electrochemical properties was investigated. Results demonstrated that the absorption band of MR-1 displayed higher extinction coefficient with a broader absorption compared to MR-2 and the benchmark Ru(II) dye, N719, due to the enhancement of electron donating ability of π-conjugated bridge. Graphical abstract: Highlights: Two novel ruthenium complexes, MR-1 andMR-2 were synthesized for use in (DSSCs). MR-1 showed the highest efficiency (8.19%) compared toMR-2 andN719 . Incorporation of terthiophene as a linker reduces the band gap ofMR-2. MR-1 displayed higher extinction coefficient with a broader absorption thanMR-2.